Smear layer removal comparing conventional irrigation, passive ultrasonic irrigation, EndoActivator System, and a new sonic device (Perfect Clean System) by scanning electron microscopy: An ex vivo study. - Bruna Fernanda Alionço Gonçalves; Divya Reddy; Ricardo Machado; Paulo César Soares Júunior; Sérgio Aparecido Ignácio; Douglas Augusto Fernandes Couto; Karine Santos Frasquetti; Vânia Portela Ditzel Westphalen; Everdan Carneiro; Ulisses Xavier da Silva Neto (PLoS ONE)
Aim This study evaluated the smear layer removal provided by conventional, sonic, and ultrasonic irrigation techniques. Methodology Forty extracted human mandibular first premolars were selected and instrumented using the ProTaper Next System files and 2.5% sodium hypochlorite. Afterward, they were divided into 4 groups (n. 10) according to the irrigation technique used to perform the final irrigation with a chelating solution (17% EDTA): conventional irrigation (CI), passive ultrasonic irrigation (PUI), EndoActivator System (EAS), and Perfect Clean System (PCS). The smear layer removal was determined through a score after evaluating scanning electron microscope images (1.000x) obtained at 1, 5, 8, and 12mm from the working length (WL). Statistical analyses were carried out by the Kruskal-Wallis and Dunn's tests with a significance level of 5% (P < 0.05). Results All irrigation techniques were unable to promote an effective smear layer removal at 1mm from the WL in comparison with the other locations (P < .05). At 5, 8, and 12mm from the WL, no statistically significant differences were observed among CI, PUI, EAS, and PCS (P > 0.05). At 12mm from the WL, statistically significant differences were only identified after comparing PCS and CI (P < .05). Conclusion The smear layer removal was only efficient at 5, 8, and 12 from the WL with no significant statistical differences among CI, PUI, EAS, and PCS (P > 0.05).